Developing mobile application for learning Malay language - Nurrul Amalina, binti Abdul Basir (Universiti Malaysia Sarawak (UNIMAS), 2015)
The advancement of mobile technology has enable language learning becomes more interactive and interesting. The development of a mobile application for learning Malay language can be used as a medium to promote Malay language to tourists from all over the world. The objectives of this project are to design and develop mobile application on learning Malay language for tourist and to evaluate the usability of the created mobile application. This project employed rapid application development to guide the development of this application. The platform used to develop the mobile application was Appnotch. The usability of the mobile application was evaluated using the formative evaluation. The method used to collect data was the think aloud protocol where participants were asked to verbalize their thought while completing a task using the mobile application. This was followed by a short interview session. Based on the participants' comments and s~ggestions, the mobile application was iteratively improved.